Comparison between Dual-X-ray Absorptiometry and Bioelectrical Impedance Analyses in dietary practice - Zborowski, Marek; Mikulec, Anna (Journal of Education, Health and Sport, 2022)
Body composition assessment is an essential part of assessing overall health, training progress, nutritional status, and monitoring the level of body fat and lean tissue content. This article is a review made to compare body composition analysis methods with the help of BIA and DXA as a dieticians’ working tool. The practical advantages of the bioimpedance method enable the wide application of this method in dietary practice. BIA can be a safe and helpful method for monitoring patient progression in terms of changes in body composition. Although DXA is currently the gold standard for measuring body composition in clinical trials, the use of this method is associated with numerous limitations resulting from the high cost of the technique, limited availability of this type of equipment and time consumption.